Bismuth-based Z-scheme photocatalytic systems for solar energy conversion. (3rd February 2021) - Guo, Lina; Huang, Hongwei; Mei, Lefu; Li, Min; Zhang, Yihe
Abstract : Charge transfer mechanism and application of Z-scheme photocatalysis. Abstract : Photocatalysis can effectively solve environmental pollution and energy supply problems by using inexhaustible sunlight. It is crucial to design high-efficiency photocatalysts with strong light-absorbing capability, strong redox potentials, high charge separation and excellent durability. Bismuth-based materials have unique crystal structures, electronic configurations and environmental friendliness. However, insufficient light absorption and charge separation greatly limit their application. Inspired by natural photosynthesis, the construction of artificial Z-scheme photocatalysts provides a feasible strategy to overcome these bottlenecks. This review mainly concentrates on the construction mechanism and structure genre of bismuth-based Z-scheme photocatalytic systems, including the liquid-phase Z-scheme photocatalytic system, all-solid-state Z-scheme photocatalytic system with a mediator, and direct Z-scheme photocatalytic system, and their applications in water splitting, CO2 reduction and pollutant degradation are summarized. The different reaction mechanisms in various applications are discussed in detail. Finally, challenges and opportunities are proposed to develop more efficient bismuth-based Z-scheme photocatalysts.